Gun violence in American society : crime, justice and public policy - Eargle, Lisa A.; Esmail, Ashraf (University Press of America Incorporated, 2016)
Gun Violence In American Society: Crime, Justice, and Public Policy provides an in-depth, multidisciplinary investigation into one of society's major social, public health and political concerns--death, injury, and destruction from the use of firearms. Contributors employ a variety of theoretical, methodological, and data analysis frameworks to address different gun violence issues, including how gun violence is created and perpetuated in society, the various forms and social contexts in which it appears, and the impact of gun violence on different social groups, communities, and social institutions. Possible solutions to gun violence are also explored.--Adapted from publisher description.